2018
DOI: 10.1002/aenm.201802190
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Power Generation and Output Optimization Criteria for Triboelectric Nanogenerators

Abstract: Triboelectric nanogenerators (TENGs) are in the forefront of next‐generation energy harvesting technologies, having been demonstrated as a leading candidate for numerous applications in energy harvesting and self‐powered sensing. However, critical parameters affecting TENG output behavior and their optimization are not well understood. Herein, for the first time, the power output characteristics of TENGs are fully unveiled by vigorously analyzing their impedance behavior as a function of excitation source and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
150
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(155 citation statements)
references
References 55 publications
4
150
1
Order By: Relevance
“…This suggests that 0.12 mm thickness is considered to be optimum for TENGs. This result is in conformation with Distance Dependent Electric Field Model (DDEF) which suggests that on increasing the thickness of dielectric layer output voltage of TENG decreases significantly [12].…”
Section: Resultssupporting
confidence: 70%
“…This suggests that 0.12 mm thickness is considered to be optimum for TENGs. This result is in conformation with Distance Dependent Electric Field Model (DDEF) which suggests that on increasing the thickness of dielectric layer output voltage of TENG decreases significantly [12].…”
Section: Resultssupporting
confidence: 70%
“…Four basic energy harvesting modes of TEHs are vertical contact-separation (CS) mode, lateral-sliding (LS) mode, single-electrode (SE) mode, and freestanding triboelectric-layer (FT) mode [ 21 ]. Examples of studies on characterization and optimization of the electrical performance of triboelectric and electrode materials, device fabrication, and environment condition control are the following studies [ 22 , 23 , 24 , 25 , 26 , 27 ]. In addition, Cun Xin Lu et al [ 28 ] investigated the temperature effect on the triboelectric electrical output of a single-electrode mode and reported that, at a low temperature, the TEH was able to generate high electrical output, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…in fact) with increasing index k. In practice, even the first three coefficients are enough to give a reasonable power estimate (relative error ≤ 15%) for all R. Clearly, the power output also depends on other parameters in the problem, for example the thickness x 1 , x 2 of the dielectrics, the excitation amplitude z 0 and the triboelectric charge density σ T . A study of the effects of these parameters and others has recently been published in [17]. This work raises some interesting questions for further investigation.…”
Section: Conclusion and Further Workmentioning
confidence: 84%
“…Here, there are just two exceptional equations because B(t) and V (t) are truncated at the first harmonic: the number of exceptional equations grows linearly with the number of harmonics retained in B(t) and V (t). There are two approaches to solving equations (17), and we explain these in the following two subsections. In the first, we show an arithmetical solution and in the second, we show how the same solution can be constructed using Bessel functions, and we briefly discuss the asymptotic behaviour of this solution.…”
Section: A Fourier Series Approachmentioning
confidence: 99%